Front Cover. Issue 7 (24th July 2018) - Lutz, James A.; Furniss, Tucker J.; Johnson, Daniel J.; Davies, Stuart J.; Allen, David; Alonso, Alfonso; Anderson‐Teixeira, Kristina J.; Andrade, Ana; Baltzer, Jennifer; Becker, Kendall M. L.; Blomdahl, Erika M.; Bourg, Norman A.; et al.
Abstract : The cover image, by James A. Lutz et al., is based on the Research Paper Global importance of large‐diameter trees, DOI: 10.1111/geb.12747 .